Răspuns :
|------|---------|----------------|
a b c
a= bile rosii
b= bile albe
c= bile albastre
a+b+c=42
a-3=b
c=(a+b)⇒ c= a+a-3⇒ c= 2a-3
se inlocuieste in relatia a+b+c=42 b si c
⇒ a+(a-3)+(2a-3)=42
a+a-3+2a-3=42
4a=42+6
4a=48
a=48:4
a=12
b=12-3
b=9
c= 2a-3
c=2*12-3
c=24-3
c=21
a+b+c=42
12+9+21=42
a b c
a= bile rosii
b= bile albe
c= bile albastre
a+b+c=42
a-3=b
c=(a+b)⇒ c= a+a-3⇒ c= 2a-3
se inlocuieste in relatia a+b+c=42 b si c
⇒ a+(a-3)+(2a-3)=42
a+a-3+2a-3=42
4a=42+6
4a=48
a=48:4
a=12
b=12-3
b=9
c= 2a-3
c=2*12-3
c=24-3
c=21
a+b+c=42
12+9+21=42
bile albe I----I-3-I
bile rosii I----I
bile albastre I----I----I-3-I
42-3-3 = 36
36:4 = 9 (bile rosii)
9+3 = 12 (bile albe)
9+12 = 21 (bile albastre)
bile rosii I----I
bile albastre I----I----I-3-I
42-3-3 = 36
36:4 = 9 (bile rosii)
9+3 = 12 (bile albe)
9+12 = 21 (bile albastre)